A Tableaux System for Dolev-Yao Multi-Agent Epistemic Logic - Fernandez, Luiz C. F.; Benevides, Mario R. F. (Anais do Workshop Brasileiro de Lógica (WBL); 2023: Anais do IV Workshop Brasileiro de LógicaDO - 10.5753/wbl.2023.230019, 2023)
Given the increasing importance of security protocols in our daily activities and communication via internet, the efforts to develop mechanisms and models for verification of such protocols are always relevant. In this work, we explore the Dolev-Yao Multi-Agent Epistemic Logic by providing a tableaux method for it. This logic is an extension of Multi-Agent Epistemic Logic, aimed to verify authenticity and safety in communication protocols and inspired by the Dolev-Yao model, a seminal work in formal cryptography.